2016
DOI: 10.1111/ijfs.13344
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing food‐based bioactive compounds to reduce the effects of ultraviolet radiation: a review exploring the link between food and human health

Abstract: Summary Appropriate exposure to sun is beneficial to humans and living organisms. However, excessive exposure to ultraviolet (UV) radiation can lead to photoageing, severe health risks and even death. Nowadays, the health risks of excess UV exposure have greatly increased due to the significant changes of global climate and human lifestyle as well as the thinning of the stratospheric ozone (a natural and effective filter for solar UV radiation). Therefore, protecting against UV radiation‐induced damage is a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 134 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…Plants, however, possess an antioxidant system that can regulate ROS levels and prevent oxidative stress. The antioxidant enzymes CAT and POD, function in the detoxification of ROS (Liu et al, ; Maya & Matsubara, ; Ye, Sun‐Waterhouse, You, & Abbasi, ), and APX also reduces oxidative stress through the AsA–GSH cycle, which catalyzes the breakdown of H 2 O 2 to water (Noctor & Foyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plants, however, possess an antioxidant system that can regulate ROS levels and prevent oxidative stress. The antioxidant enzymes CAT and POD, function in the detoxification of ROS (Liu et al, ; Maya & Matsubara, ; Ye, Sun‐Waterhouse, You, & Abbasi, ), and APX also reduces oxidative stress through the AsA–GSH cycle, which catalyzes the breakdown of H 2 O 2 to water (Noctor & Foyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are different groups of biologically active polyphenols in grape pomace, including flavonoids phenolic acids, and condensed tannins (Abbasi et al, ; de Oliveira et al, ; Ye, Sun‐Waterhouse, You, & Abbasi, ). The most common flavonoids found in grapes are anthocyanins and variations in their chemical structures implies their high reactivity during food processing, being highly sensitive to acidity (Putnik, Bursać Kovačević, & Dragović‐Uzelac, ), heat and oxidative degradation (Bursać Kovačević, Putnik, Dragović‐Uzelac, et al, ; Patras, Brunton, O'donnell, & Tiwari, ; Ricci, Parpinello, & Versari, ) therefore their extraction from plant cells is an important task closely associated to the need of preservation their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also reported the antioxidant properties of grapes (Boussetta, Lanoisellé, Bedel‐Cloutour, & Vorobiev, ; Goula, Ververi, Adamopoulou, & Kaderides, ; Rockenbach, Gonzaga, et al, ; Rockenbach, Rodrigues, et al, ). The antioxidant compounds are very important, since they can scavenge hydroxyl radicals and superoxide anion radicals, preventing dangerous diseases like cancer (Gengaihi, Ella, Emad, Shalaby, & Doha, ; Kong, Chia, Goh, Chia, & Brouillard, ), and UV‐induced damages such as skin diseases, blindness, and immune system resistance reduction (Ye, Sun‐Waterhouse, You, & Abbasi, ). As a somewhat more indirect health benefit, grapes can also be used as a natural alternative to food dyes, since their skin is rich in anthocyanins (Bleve et al, ).…”
Section: Introductionmentioning
confidence: 99%